Antioxidant Activity Test of Ethyl Acetate Extract of Avocado Seeds (Persea americana Mill.) Using the 1,1-Diphenyl-2-Picrylhdrazyl Method - Rahmat, Sri Rahayu; Pratama, Mamat (Pharmaceutical Reports, 2024)
Avocado is a plant that can thrive in tropical areas such as Indonesia and is one of the types of fruit that is popular with the public, however, avocado seeds have not been used optimally so that they are wasted as waste. Based on phytochemical experiments, avocados also contain phenolics, tannins and flavanoids which have antioxidant activity. Antioxidants are compounds that can be used to counteract free radicals. Dietary fiber and antioxidants are two types of components that are very useful in improving health and being able to prevent various diseases. The extraction method used in this study is reflux where the sample is heated for 6 hours with the solvent used to evaporate at high temperatures, but it will be cooled by the condenser so that the solvent which was in the form of vapor will condense in the condenser and fall again into the reaction vessel so that the solvent will still be there during the reaction. This study aims to analyze the antioxidant activity of the ethyl acetate extract of avocado seeds using the DPPH method. Quantitatively, the ethyl acetate extract of avocado seeds (Persea americana Mill.) was measured at a maximum wavelength of 516 nm using quercetin as a reference standard. The research results showed that the value was 903.08 μ/mL. Quantitatively, the ethyl acetate extract of avocado seeds (Persea americana Mill.) was measured at a maximum wavelength of 516 nm using quercetin as a reference standard. The research results showed that the value was 903.08 μ/mL. Quantitatively, the ethyl acetate extract of avocado seeds (Persea americana Mill.) was measured at a maximum wavelength of 516 nm using quercetin as a reference standard. The research results showed that the value was 903.08 μ/mL.